Percutaneous retrieval of intracardiac fragmented hemodialysis catheter using a snare-loop catheter: A case report - Adhitya Ginting; Ketut Putu Yasa; Yan Efrata Sembiring (Faculty of Medicine, Universitas Islam Indonesia, 2020)
We presented a 60-year-old woman with an history of end-stage renal disease on regular hemodialysis, twice a week, came with a tunneled dialysis catheter (TDC) that was attached to the right internal jugular vein. TDC has been dysfunction since one week ago that was suspected as a result of thrombosis in the lumen of TDC. TDC was cut in the insertion of the jugular vein. And then a wire was inserted into TDC that has been cut off. From Chest x-ray imaging, migration of fragmented TDC was found inside the heart chamber with wire inside the lumen. Fluoroscopy showed a picture of a fragmented TDC in the heart chamber with a wire inside the lumen. Retrieval of fragmented TDC used percutaneus snare loop method with wire guiding that was inserted through the left femoral vein. Fragmented TDC was removed successfully. Retrieval of the fragmented TDC through endovascular techniques is classified as a simple. Simple snare loop method is quite effective and very cheap compared to the commercial snare, open surgery or laparoscopic surgery that can be avoided.